KIWIRA MARKET, an interface emphasizing African urban-rural interactions - (:unkn) unknown (My University, 2015)
The market of Kiwira, located in the Uporoto Mountains, Tanzanian, is a hotspot of exchanges, both social and economic. It is a starting point and in a lesser extent an ending point. It is a symbol of the amplification of agriculture and of the integration of rural areas to the national territory and to the global economy through urbanisation and access to the market. Kiwira, like the majority of bustling African markets, is an interface that structures urban-rural dynamics articulating several geographical scales; in other words, it is a medium adjusting the face-to-face encounter of several dimensions of society.
Keywords: African Research